ANALISIS YURIDIS TERHADAP PASAL 37 UUJN-P NOMOR 2 TAHUN 2014 TENTANG JABATAN NOTARIS DAN KODE ETIK NOTARIS MENGENAI SANKSI BAGI NOTARIS YANG MENOLAK MEMBERIKAN JASA HUKUM SECARA CUMA-CUMA KEPADA ORANG YANG TIDAK MAMPU - FLORENCE PERMENTA BR MANIK (Magister Kenotariatan, Universitas Jambi, 2021)
ABSTRACT Chapter 37 verse 1 and 2 UUJN-P describe that Notary have to give help for free about the Notary to person who is not able to pay. Notary who break the rules in verse 1 can be punished by spoken reminder, written reminder, temporary disbanned, either wise the chapter isn't describe in detail about the kind of legal service the Notary have to give for free and the criteria of the person who is not able to pay the fee, so the rules will burden the Notary itself. The formulation of the problem in this study is what's the main meaning of legal service which is given by the Notary for free, in terms of the Determination of the implementation of the legal service for free to the people who is not able to pay the fee in their working area and how is the analysis of the chapter 37 UUJN-P and Notary ethics code regarding the sanctions for the notaries who refuse provide legal service for free. This observation is using the juridical empirical observation. The chapter 37 UUJN-P don't tell us spesifically about what is the free legal service as what they can give to person who is not able to pay, but logically the conclusion is the legal service which the Notary can give to the person who is not afford to pay is like the law consultation and law counceling. This is happened because if the legal service as document making give to person who is not afford to pay feels so hard to Notary himself. The analysis of Article 37 of the UUJN-P and the Notary Ethics Code that it is appropriate that notaries should provide free legal services in the form of legal counseling and legal consultation to the public, because notaries are a noble profession, but in terms of providing legal services in the form of a notary deed , then there should be no compulsion to the notary to provide legal services in the form of making a deed for Free, bearing in mind that not all notaries have sufficient finances. Even if it is required to provide assistance in the form of legal services for free, the government should intervene in this matter. Keywords: Free, Legal Services, Notary Public